2020
DOI: 10.1007/s00234-020-02526-5
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of long-term recurrent ischemic stroke: the added value of non-contrast CT, CT perfusion, and CT angiography

Abstract: The aim of this study was to evaluate whether the addition of brain CT imaging data to a model incorporating clinical risk factors improves prediction of ischemic stroke recurrence over 5 years of follow-up. Methods A total of 638 patients with ischemic stroke from three centers were selected from the Dutch acute stroke study (DUST). CT-derived candidate predictors included findings on non-contrast CT, CT perfusion, and CT angiography. Fiveyear follow-up data were extracted from medical records. We developed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Although stroke has a variety of clinical symptoms, the use of neuroimaging in patient examination, diagnosis, and treatment is a major theme in modern IS care, and neuroimaging is widely used to assess vascular patency and tissue vitality. For instance, data from CT imaging have significantly improved the discriminatory performance and reclassification for predicting IS recurrence beyond a model incorporating clinical risk factors only [ 15 , [18] , [19] , [20] ]. Regional data in China revealed that the rate of neuroimaging diagnosis and hospitalisation of stroke patients have increased significantly over the past three decades, with an annual increase of 4.0% and 11.2%, respectively [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although stroke has a variety of clinical symptoms, the use of neuroimaging in patient examination, diagnosis, and treatment is a major theme in modern IS care, and neuroimaging is widely used to assess vascular patency and tissue vitality. For instance, data from CT imaging have significantly improved the discriminatory performance and reclassification for predicting IS recurrence beyond a model incorporating clinical risk factors only [ 15 , [18] , [19] , [20] ]. Regional data in China revealed that the rate of neuroimaging diagnosis and hospitalisation of stroke patients have increased significantly over the past three decades, with an annual increase of 4.0% and 11.2%, respectively [ 21 ].…”
Section: Discussionmentioning
confidence: 99%